Perception of social support and psychotic symptoms among persons with schizophrenia: A strategy to lessen caregiver burden. (November 2019) - Peng, Man-Man; Zhang, Tian-Ming; Liu, Ke-Zhi; Gong, Ke; Huang, Chao-Hua; Dai, Guang-Zhi; Hu, Shi-Hui; Lin, Fu-Rong; Chan, Sherry Kit Wa; Ng, Siuman; Ran, Mao-Sheng
Background: Improving patients' perception of social support is significant not only for their re-adaptation to life but also for alleviating caregivers' burden. Aim: This study aims to examine an integrated model regarding social support, psychotic symptoms and caregiver burden. Methods: Persons with schizophrenia ( N 1 = 300) and their family caregivers ( N 2 = 300) in Xinjin County, Chengdu, China, completed the survey to report their demographics, patients' perception of social support (Duke Social Support Index), psychotic symptoms (Positive and Negative Syndrome Scale) and caregiver burden (Burden Scale for Family Caregivers, Short Version). Structural equation modelling was utilised to test the proposed model. Results: The degree of caregiver burden differed significantly within subgroups of patients' gender and education, as well as caregivers' gender, education and employment. Caregiver burden was negatively related to patients' age and household income. Social interaction partially mediated the relationship between instrumental and subjective social support (total effect = 0.451, p < .01). Subjective social support fully mediated the impact of social interaction on psychotic symptoms (total effect = −0.099, p < .05). In the final model, instrumental social support was positively associated with social interaction ( p < .001) and increased subjective social support ( p < .05). Increased subjective social support showed correlation with a lower degree of psychotic symptoms ( p < .01), which was related to a lower level of caregiver burden ( p < .001). Conclusion: This study shows the associations of patients' social support with psychotic symptoms and caregiver burden. Culture-specific psychosocial interventions should be provided for both patients and caregivers to enrich external support and reduce psychotic symptoms and caregivers' burden within the health care environment.